Atenuação do reflexo Bezold-Jarisch após tratamento crônico com doses suprafisiológicas de decanoato de nandrolona em ratos sedentários - Medeiros, Ana Raquel Santos de (2007)
While there clinical applications of anabolic-androgenic steroids (AAS), the misuse of AAS is widespread and is not limited to competitive athletes but the majority of AAS abusers are noncompetitive recreational bodybuilders and even nonathletes. Objective: we investigated the influence of treatment with an AAS on the BezoldJarisch reflex (BJR) control of heart rate (HR) and whether this treatment induced cardiac hypertrophy and anabolic effects in rats. Methods: male rats were treated with nandrolone decanoate (ND; 10 mg.Kg-1 body weight/8 wks; DECA) or vehicle control (CON). After 8 wks, the BJR was evaluated by bradicardia responses elicited by serotonin administration (2-32 µg.Kg-1). Mean arterial pressure (MAP) was assessed and cardiac hypertrophy was determined by the left or right ventricle weight/body weight (LVW/BW; RVW/BW; respectively). The measurement of the total body protein content of the animals was performed. Results: ND treatment determined an elevation of the MAP of DECA animals compared with CON group (CON = 99 ± 1; DECA = 109 ± 2 mmHg; p<0.01). There was no change in the mean basal HR of DECA animals (CON = 356 ± 13; DECA = 367 ± 11 bpm). The LVW/BW and RVW/BW ratios indicated significant hypertrophy of the LV and RV in DECA animals (CON = 1.86 ± 0.04, DECA = 2.17 ± 0.04, p<0.01; CON = 0.42 ± 0.02, DECA = 0.53 ± 0.03 mg.g-1, p<0.05; respectively). Total body protein content was enhanced in DECA group compared with CON rats (CON=18.2 ± 1%, DECA = 28.0 ± 1%; p<0.01). In the last two doses of serotonin the BJR control of HR was significantly blunted in DECA rats compared with CON group (CON = -61 ± 4% and -76 ± 3%; DECA = -47 ± 4% and -66 ± 3%; p<0.01 and p<0.05, respectively). Conclusions: We conclude that 8-wks ND treatment induces an anabolic effect, cardiac hypertrophy and an elevation of the MAP in DECA rats. The treatment 15 reduces the sensitivity of the BJR control of bradicardia, what could be explained by the presence of a cardiac hypertrophy and/or an elevated MAP in DECA animals.